Luta resistência de uma educadora persistente - Nunes, Iracema da Cruz (Brasil, 2024)
This academic memorial constitutes an autobiographical narrative resulting from surveys of my trajectory through early childhood, elementary and academic education, reporting the experiences acquired over these years, considering that the facts presented deal with memories of this path taken and the main contributions to my personal development . Its purpose is to highlight the difficulties, differences between adaptations and present perceptions in higher education, and the methodology applied in this study. These are memories referring to the educational trajectory presented by reports and photographs, authorships, where the perception of teaching methods are visualized as results and their positive and negative character in the student's life is concluded depending on their application or absence.